Early Detection of Cercospora Species in Soybean Plants: Immunologic and Molecular Methods - Latorre Rapela, María Gabriela de Los Milagros (2015)
Late-cycle diseases (LCD) cause a significant deterioration in quality and reduce yields in soybean crops. In Argentina, in particular, leaf blight and purple seed stain, caused by the agent Cercospora kikuchii, and frog eye spot, caused by C. sojina, are the prevailing sources of diseases. The early,rapid and accurate detection of these phytopathogens becomes essential, and would contribute to preserving both the environment and the health of humans and animals by preventing the wasteful or improper use of chemicals such as pesticides. In order to detect Cercospora species in soybean plants at an early stage, immunochemical and molecular techniques were developed in this work. Strains from the NITE Biological Resource Center collection (Japan): Cercospora kikuchii NBRC 6711 and Cercospora sojina NBRC 6715 and regional isolates of C. kikuchii were used. To develop Dot-Blot and PCR techniques, experiments with plants undergoing different treatmentswere carried out: those experimentally inoculated with these fungi, those treated with sterile water and healthy plants as well. Both techniques allowed the detection, at early stages, of Cercospora species involved in two of the most frequent LCD in the country, when the cercosporin concentration produced by the fungus was higher than 3.93 ± 0.39 nmol∙cyl−1 ±SD. The sensitivity between both techniques was very different. While Dot-Blot allowed the detection of the disease 4 days after inoculation, PCR detected it after 4 hours, even without visible symptoms of the disease.